Coccidiose em cães e gatos do município de andradina, estado de são paulo, Brasil - Coelho, Willian Marinho Dourado [UNESP]; do Amarante, Alessandro Francisco Talamini [UNESP]; Perri, Silvia Helena Venturoli [UNESP]; Coelho, Natalia Marinho Dourado [UNESP]; Apolinário, Juliana de Carvalho [UNESP]; Teixeira, Weslen Fabricio Pires [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (My University, 2012)
Coccidiosis is one of the most common parasitic diseases in dogs and cats in all the world. The aim of this study was to determine the occurrence of this parasitosis in dog and cat population at the Municipality of Andradina in the State of São Paulo, from 2007 to 2009. Fecal samples from 97 cats and 93 dogs were analyzed by using the techniques of flotation in saturated sodium chloride and spontaneous sedimentation. The species were classified according to morphology of the oocysts. Cystoisospora fecal oocyst found in 71.1% (69/97) of the cats, and simple infection by C. rivolta and C. felis occurred respectively in 41.0% (16/39) and 20.5% (8/39) animals, with P ≥ 0.2319. In 39.7%(37/93) of the dogs was found positive for Cystoisospora spp. And the species C. canis identified in the largest proportion (63.9%) with P = 0.0005. From the results, we conclude that dogs and cats had high incidence of infection Cystoisospora, being C. canis and C. rivolta most observed species, respectively.
Coccidiosisin dogs and cats at the municipality of andradina in the state of são paulo, Brazil
Keywords: Coccidia. cystoisosporinae. natural infection. companion animals; Animalia; Canis familiaris; Coccidia; Cystoisospora; Cystoisospora rivolta